Temperature dependence of raman scattering in 4H-SiC films under different growth conditions - Wang, H.C.; He, Y.T.; Sun, H.Y.; Qiu, Z.R.; Xie, D.; Mei, T.; Tin, C.C.; Feng, Z.C. (Iop Publishing Ltd, Temple Circus, Temple Way, Bristol Bs1 6be, England, 2015)
The microRaman scattering of 4H-SiC films, fabricated by low pressure chemical vapor deposition under different growth conditions, is investigated at temperatures ranging from 80K to 550 K. The effects of growth conditions on E-2(TO), E-1(TO) and A(1)(LO) phonon mode frequencies are negligible. The temperature dependences of phonon linewidth and lifetime of E2(TO) modes are analyzed in terms of an anharmonic damping effect induced by thermal and growth conditions. The results show that the lifetime of E-2(TO) mode increases when the quality of the sample improves. Unlike other phone modes, Raman shift of A(1) (longitudinal optical plasma coupling (LOPC)) mode does not decrease monotonously when the temperature increases, but tends to blueshift at low temperatures and to redshift at relatively high temperatures. Theoretical analyses are given for the abnormal phenomena of A(1)(LOPC) mode in 4H-SiC.